2022
DOI: 10.1186/s13045-022-01302-7
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and incident cardiovascular events after next-generation BTKi therapy initiation

Abstract: Background Post-market analyses revealed unanticipated links between first-generation Bruton’s tyrosine kinase inhibitor (BTKi) therapy, ibrutinib, and profound early hypertension. Yet, whether this is seen with novel selective second (next)-generation BTKi therapy, acalabrutinib, is unknown. Methods Leveraging a large cohort of consecutive B cell cancer patients treated with acalabrutinib from 2014 to 2020, we assessed the incidence and ramificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…127 Importantly, the study demonstrated there was no single antihypertensive treatment which was found to prevent this hypertensive effect. 127 These opposing data presented support the need for further larger clinical trials and real-world studies to properly ascertain the true hypertensive effects of the newer generation BTKi treatments. hypertension is limited.…”
Section: Clinical and Epidemiological Evidence For Btki-induced Hyper...mentioning
confidence: 97%
“…127 Importantly, the study demonstrated there was no single antihypertensive treatment which was found to prevent this hypertensive effect. 127 These opposing data presented support the need for further larger clinical trials and real-world studies to properly ascertain the true hypertensive effects of the newer generation BTKi treatments. hypertension is limited.…”
Section: Clinical and Epidemiological Evidence For Btki-induced Hyper...mentioning
confidence: 97%
“…Unlike most AEs, which have the highest onset in the first year of BTK inhibitor therapy, the incidence of new onset hypertension increases over the course of treatment [ 79 ]. In addition, higher rates of hypertension have been reported in real-world studies, with up to 78% of patients receiving ibrutinib and 49% receiving acalabrutinib having new or worsened hypertension [ 80 , 81 , 82 ]. Risk factors for the development of new hypertension based on multivariable analysis include prior arrhythmias and Black ancestry [ 82 ].…”
Section: Adverse Events: Frequency and Managementmentioning
confidence: 99%
“…In addition, higher rates of hypertension have been reported in real-world studies, with up to 78% of patients receiving ibrutinib and 49% receiving acalabrutinib having new or worsened hypertension [ 80 , 81 , 82 ]. Risk factors for the development of new hypertension based on multivariable analysis include prior arrhythmias and Black ancestry [ 82 ]. In real-world studies, new or worsened hypertension was also associated with increased risk of major adverse cardiovascular events (MACE) [ 82 ].…”
Section: Adverse Events: Frequency and Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypertension, as characterized by elevated blood pressure (140/90 mmHg), is a leading powerful risk factor for cardiovascular diseases [ 1 , 2 ]. Unfortunately, the cure rate of hypertension in the world is still unsatisfactory.…”
Section: Introductionmentioning
confidence: 99%